Simultaneous Estimation of Dolutegravir Sodium, Emtricitabine, and Tenofovir Disoproxil Fumarate by UPLC - Annapurna, Dr. Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: A new reversed-phase ultra-fast liquid chromatography (RP-UPLC) method has been developed for the simultaneous quantification of Dolutegravir sodium, Emtricitabine, and Tenofovir disoproxil fumarate. Dolutegravir, Emtricitabine, and Tenofovir disoproxil fumarate are anti-retroviral drugs. Dolutegravir sodium is an human immunodeficiency virus integrase inhibitor. Emtricitabine and Tenofovir disoproxil fumarate are reverse transcriptase enzyme inhibitors. Materials and Methods: Shimadzu NexeraX2 Model UPLC system with PDA detector and Shim-pack C18 column was employed for the chromatographic study. Mobile phase consisting of 0.1% Tri ethyl amine (Adjusted to pH 6.0 with ortho phosphoric acid): Acetonitrile (55: 45) was used with 1.0 mL/ min flow rate and UV detection at 260 nm. Results and Discussion: Beer-Lambert’s law was obeyed over the concentration range 5–400, 2–150 and 5–500 μg/mL with linear regression equation y = 1211.7× + 506.73 (R² = 0.9998), y = 3330.4×–1162.3 (R² = 0.9999), and y = 1262.7× + 990.03 (R² = 0.9998) for tenofovir disoproxil fumarate, dolutegravir sodium, and emtricitabine, respectively, and the method was validated as per ICH guidelines. The total run time was 5 min. The limit of quantitation values was found to be 1.9113, 4.8752, and 4.7654 μg/mL and that of the limit of detection values 0.6287, 0.1598, and 0.1568 μg/mL for tenofovir disoproxil fumarate, dolutegravir sodium, and emtricitabine respectively. The proposed RP-UPLC method is simple, precise, and accurate. This method can be used for the regular analysis of pharmaceutical dosage forms. Conclusion: The proposed RP-UPLC method is simple, precise, and accurate. This method can be used for the regular analysis of pharmaceutical dosage forms.